Swipe & Scroll Bijak Melawan Hoaks Pemilu 2024 di Sosial Media - Ummah, Innisa Khofifatul; Putri, Putu Indah Dianti (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The "Swipe & Scroll Wisely Against Election Hoaxes 2024" program in Padangsambian Klod, Denpasar, Bali, aims to enhance the community's digital literacy and political awareness. Facing the 2024 Elections, this initiative educates about information verification and the impact of social media on democracy. Utilizing Instagram as a social media platform, the program produces educational content, facilitates online discussions, and fosters a critical community. Its impact is evident from the improved ability to identify hoaxes and increased participation in political discussions, as well as the formation of digital volunteers for ongoing digital literacy campaigns.